2010
DOI: 10.1007/s11664-010-1441-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dopant on Growth of Intermetallic Layers in Sn-Ag-Cu Solder Joints

Abstract: The interfacial interaction between Cu substrates and Sn-3.5Ag-0.7Cu-xSb (x = 0, 0.2, 0.5, 0.8, 1.0, 1.5, and 2.0) solder alloys has been investigated under different isothermal aging temperatures of 100°C, 150°C, and 190°C. Scanning electron microscopy (SEM) was used to measure the thickness of the intermetallic compound (IMC) layer and observe the microstructural evolution of the solder joints. The IMC phases were identified by energy-dispersive x-ray spectroscopy (EDX) and x-ray diffractometry (XRD). The gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…They found that antimony increases the activation energy of Cu 6 Sn 5 layer formation, reduces the atomic diffusion rate and thus inhibits the excessive growth of intermetallic compounds. The authors suggested that the effect of Sb additions can be explained by grain boundary obstruction mechanism [24]. Similarly, Rizvi et al observed a beneficial effect of bismuth additions in Sn-Ag-Cu solder alloy on the decrease of intermetallic layer growth [25].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…They found that antimony increases the activation energy of Cu 6 Sn 5 layer formation, reduces the atomic diffusion rate and thus inhibits the excessive growth of intermetallic compounds. The authors suggested that the effect of Sb additions can be explained by grain boundary obstruction mechanism [24]. Similarly, Rizvi et al observed a beneficial effect of bismuth additions in Sn-Ag-Cu solder alloy on the decrease of intermetallic layer growth [25].…”
Section: Introductionmentioning
confidence: 95%
“…The influence of dopant on the growth of intermetallic layers in Sn-Ag-Cu solder joints with copper has recently been inves- tigated by Li et al [24] The authors studied the interactions of Sn-3.5Ag-0.7Cu-xSb alloys with different antimony concentrations (0.2-2.0%) [24]. They found that antimony increases the activation energy of Cu 6 Sn 5 layer formation, reduces the atomic diffusion rate and thus inhibits the excessive growth of intermetallic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The integration in electronic assemblies is ever-increasing, resulting in reduced component sizes and higher power density [1]. The industry requires lead-free soldering technology solutions to provide reliable solder joints even at elevated temperatures, such as in the case of power LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Paixao et al [27] reported that a small addition of Sb (1-2 wt%) to Sn-Bi solder refined the dendritic and eutectic structures and increased yield strength and ultimate tensile strength because Sb dissolved in the Sn matrix and formed an SnSb solid solution. SnSb solid solutions can increase the rate of nucleation and refine the microstructure of solder alloys [28][29][30]. Chaojun et al [31] reported that large amounts (25-31wt%) of Sb added to Sn-3.0Ag-0.5Cu (SAC305) solder formed large SnSb phases and Ag 3 (Sn, Sb) IMCs in the solder matrix.…”
Section: Introductionmentioning
confidence: 99%